User Satisfaction Analysis of MyTelkomsel Application using Importance-Performance Analysis (IPA) and End-User Computing Satisfaction (EUCS) Methods - Maulana, Bima; Rahmawita, Medyantiwi; Syaifullah, Syaifullah; Jazman, Muhammad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study was conducted to analyze user satisfaction with the MyTelkomsel application using the End-User Computing Satisfaction (EUCS) and Importance-Performance Analysis (IPA) methods. The EUCS approach was employed to evaluate user satisfaction based on five key dimensions: content, accuracy, format, ease of use, and timeliness. Meanwhile, the IPA method was applied to identify features that require improvement based on the levels of importance and performance perceived by users. A quantitative method was used in this study, involving data collection through questionnaires distributed to active MyTelkomsel users. The results of the study revealed several dimensions that significantly contribute to user satisfaction, as well as areas that require prioritized improvements to enhance the quality of the application. The researchers hope that the findings of this study will assist developers in improving the application's quality to boost user satisfaction and loyalty.